EFFECTS OF PROBIOTIC AND ORGANIC FERTILIZERS AS SOIL AMENDMENTS ON THE GROWTH AND YIELD OF WHEAT (Applied Biological Research, 2023)
Present study aimed to comprehensively assess the impact of organic  amendments on crop health without compromising on growth and yield. To  evaluate the effect of organic amendment a comprehensive study in wheat  was conducted in a randomized complete block design with three replications  for three consecutive wheat growing seasons (2017-2019). The experiment  comprised of was nine soil amendment treatments wherein organic manures,  probiotics and chemical fertilizer were used. The dry matter accumulation,  leaf area index, and crop growth rate were assessed at 25, 40, 55, 70 and 85  days after sowing (DAS). At 85 DAS, the maximum TDM accumulation  (769.89 g m-2) was recorded by the chemical fertilizer which was statically  similar (752.48 g m-2) with poultry manure + vermicompost + green manure  (Sesbania rostrata). Similar trend was found in case of LAI (4.07 followed by  3.84) at 55 DAS. Likewise, the maximum CGR 20.30 and 19.07 g m-2 d-1 was  noted at 55-70 DAS under the same treatment condition. The study revealed  that the growth attributes significantly increased in chemical fertilizer than  poultry manure + vermicompost + green manure treatment and untreated  control. Application of probiotic and organic manures significantly  influenced the growth attributes of wheat. The information generated is very  useful for farmers and agriculturist for enhancing the growth and yield of
Keywords: Green and poultry manure; growth attributes; probiotics; vermicompost; yield; wheat